State v. Carswell: The Whipsaws of Backlash - Marc Spindelman (Washington University Journal of Law & Policy, 2007)
When, late in April 2006, the Ohio Supreme Court agreed to hear State v. Carswell—a case in which the court will decide whether Ohio’s recently enacted “Marriage Amendment” abolishes the protections unmarried victims of domestic abuse currently receive under state law—it set the stage to deliver cultural conservatives some bad news. Virtually no matter how the court rules, they will lose, setting back their efforts in Ohio and elsewhere to pass and enforce anti-gay marriage amendments, as well as the larger reclamation project of which they have been (and are) a part: the push to redistrict the law as a zone of traditional morality.
Keywords: Unmarried couples -- Ohio; Family violence -- Ohio; Domestic violence; Gay couples; Husband and wife (Law); Same-sex marriage; Unmarried couples; Ohio. Constitution; Ohio; State v. Carswell